The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c4cc03615h
|View full text |Cite
|
Sign up to set email alerts
|

Pd(ii)-Catalyzed arylation of unactivated methylene C(sp3)–H bonds with aryl halides using a removable auxiliary

Abstract: A Pd(II)-catalyzed arylation of methylene C(sp(3))-H bonds in aliphatic amides directed by our newly developed PIP directing group with aryl iodides/bromides has been achieved. Arylation occurs efficiently with a broad range of aryl halides and amides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 58 publications
0
36
0
4
Order By: Relevance
“…To achieve high enantioselectivity, the chiral ligands should be capable of creating a steric environment that induces stereocontrol and of accelerating or enabling the cleavage of C−H bonds . We previously disclosed a Pd‐catalyzed arylation of secondary C(sp 3 )−H bonds with aryl bromides assisted by our newly developed 2‐pyridinylisopropyl (PIP) auxiliary . The use of PivOH as the ligand significantly improved the reactivity [Eq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve high enantioselectivity, the chiral ligands should be capable of creating a steric environment that induces stereocontrol and of accelerating or enabling the cleavage of C−H bonds . We previously disclosed a Pd‐catalyzed arylation of secondary C(sp 3 )−H bonds with aryl bromides assisted by our newly developed 2‐pyridinylisopropyl (PIP) auxiliary . The use of PivOH as the ligand significantly improved the reactivity [Eq.…”
Section: Methodsmentioning
confidence: 99%
“…To test this hypothesis, we commenced our investigations by replacing PivOH with L2 under reaction conditions that we had previously reported (Table ) . Thus, upon using butyric amide 1 a and p ‐acetylbromobenzene ( 2 a ) as the model system, the desired β‐arylation product 3 aa was afforded in 55 % yield and 30:70 e.r.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we evaluated the potential of other known directing groups in assisting this transformation, including the perfluoroaniline, 2‐(pyridine‐2‐yl)‐isopropylamine, 2‐methylthioaniline, picolinamide, 2‐aminopyridine N ‐oxide, and 2‐(4,4‐dimethyl‐4,5‐dihydrooxazol‐2‐yl)aniline . We found that none of those groups were effective in directing the amination under the reaction conditions (see the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…An alternative, yet reliable and scalable, procedure for the preparation of PIPamine was established according to the modification of a reported procedure using MeMgBr as the nucleophilic reagent. 2 To a solution of 2-cyanopyridine (33.0 g, 0.32 mol) in 500 mL of toluene was added CH 3 MgBr (3.2 M in 2-methyltetrahydrofuran, 300 mL, 0.96 mol) slowly at 0 • C under nitrogen (eq 2). Upon completion of the addition, the mixture was refluxed overnight.…”
Section: Use Of Memgbr As Nucleophilicmentioning
confidence: 99%
“…12 Bromoalkynes can be used as the alternative alkynylation reagents when nickel was used as the catalyst. The nickelcatalyzed alkynylation of a broad range of benzamides with bromoalkynes proceeded efficiently with low nickel loading (0.5 mol % Ni(OTf) 2 More recently, a nickel-catalyzed oxidative alkynylation of (hetero)aromatic C-H bonds with terminal alkynes under atmospheric pressure of oxygen assisted by PIP auxiliary was disclosed. Relative to the previous copper-mediated oxidative alkynylation, this protocol features the use of catalytic amount of nickel as catalyst and oxygen as the sole oxidant.…”
Section: C-o Bond Formationmentioning
confidence: 99%